9-Fluorenemethanol: an internal electron donor to fine tune olefin polymerization activity - Gnanakumar, Edwin S.; Chokkapu, Eswara Rao; Kunjir, Shrikant; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Chakraborty, Debashis; Gopinath, Chinnakonda S. (Dalton Transactions, 2014)
A new MgCl2 based molecular adduct has been synthesized with 9-fluorenemethanol (9FM) as a novel internal electron donor (IED), along with ethanol (EtOH) (MgCl2 center dot n9FM center dot xEtOH). The above molecular adduct has been subjected to a variety of structural, spectroscopic and morphological characterization techniques. The results of the solid state C-13 CPMAS NMR technique suggests the coordination of 9FM to MgCl2. Observation of a low angle diffraction peak at 2 theta = 5.7 degrees (d = 15.5 angstrom) underscores the coordination of 9FM along the z-axis, and ethanol in the molecular adduct. Active Ziegler-Natta catalysts were prepared by two different synthesis methods; the conventional method to obtain a high surface area active catalyst, and other one with 9FM as an integral part of the active catalyst in order to study the influence of 9FM as an IED over the active sites. The active catalysts were also characterized thoroughly with different analytical tools. The XRD results show (003) facets of delta-MgCl2 (alpha-MgCl2) for the conventional (non-conventional) titanated catalyst. Results of the ethylene polymerization activity study reveals that the conventionally prepared highly porous active catalyst shows 1.7-2.5 times higher activity than the non-conventional prepared catalyst; however, the latter shows a low molecular weight distribution and confirms the role of the Lewis base as an IED.